Metabolic and ventilatory thresholds assessment in front crawl swimming - Ribeiro, J.; Figueiredo, P.; Sousa, M.; De Jesus, K.; Keskinen, K.; Vilas-Boas, J. P.; Fernandes, R. J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to assess and characterize the ventilatory anaerobic threshold in swimming, and to verify if the anaerobic metabolic threshold could be accurately estimated using ventilatory parameters.